Effect of N.P.K and organic manure &on plant growth in Dragon fruit (Hylocereu polyrhizus) under Kanpur agro climatic condition cv. Red Flesh (International Journal of Food and Nutritional Sciences, 2023)
In winter 2022–2023, a study titled "Studies on N.P.K and organic manure on plant growth and establishment of dragon fruit (Hylocereus polyrhizus) under Kanpur agro climatic condition" cv. Red Flesh was carried out at the research farm of the Department of Horticulture, Rama University, Kanpur. The 11 treatments in the experiment were duplicated three times and were set up in a randomized block design. therapies that include viz.Using T0 as the control, T1 as NPK (100%RDF), T2 as NPK (50%RDF)+45% FYM, T3 as NPK (50% RDF)+45% poultry manure, T4 as NPK (50% RDF)+45% vermicompost, T5 as NPK (25% RDF)+65%FYM, and T6 as NPK (25% RDF)+65% vermicompost +65% FYM (25 percent RDF) +65% poultry manure, T7 = 100% F.Y.M., T9 = 100% vermicompost, and T10 = 100% poultry manure. Plant canopy north to south (16.44cm3), plant canopy east to west (19.38cm3), maximum plant height (46.78 cm), number of branches (4.23), and main stem circumference (22.54cm) were all revealed by the results number of sprouting (6.35), New shoots height (58.11), and survival percentage (100%) of plantwere recorded in T4 (NPK(50% RDF)+50% vermicompost) followed by T3 (NPK (50% RDF)+50% poultry manure). The least values were recorded in the control